CONTROLE DA CORRUPÇÃO: COMO RESPONDER DE FORMA MAIS COMBATIVA A ESTE FENÔMENO (Reflection and Critique Law Magazine, 2022)
The present work has as its research theme the forms of control of public administration in the fight against corruption. The Federal Constitution of 1988 provides for internal and external control of administrative activity, but increasingly the feeling of institutionalization of corruption is being addressed. There is a need to revisit the constitutional text to ensure the ideals provided for there. Thus, in order to answer the following problem: how could public administration be more combative in the face of the corruption phenomenon?, an approach on Public Administration and its forms of control will be carried out. Then, important aspects about corruption and internal control as a form of combat will be outlined. Finally, a case study will be made of a decision taken from the website of the Court of Auditors of the State of Rio Grande do Sul in relation to the management accounts of the chief executive. The deductive research method will be used and the bibliographic technique will be used.